Verbal Bullying in Harald Zwart's Film "The Karate Kid" (2010): A Critical Analysis - Alkadrie, Muhammad Zaheer; Atthariq, Ibrahim (Persepsi: Communication Journal, 2025)
This study aims to analyze the causes and effects of verbal bullying depicted in The Karate Kid (2010) using a descriptive method. The film portrays Dre, a transfer student from the United States, as a victim of verbal bullying by Cheng and his friends. The analysis is based on theories from Wardhana (2015) and Fujikawa (2016). The identified causes of verbal bullying include Cheng's hatred toward Dre's physical differences, Cheng's lack of self-confidence driving him to seek attention, and his resentment stemming from negative experiences with his teacher. The effects of verbal bullying on Dre include feeling intimidated, leading him to avoid Cheng, and feeling alienated, which causes discomfort in his new environment and a desire to return to the United States. This study highlights the complex causes and significant psychological impacts of verbal bullying, both in real-life contexts and fictional representations such as films.